The Use Of Sharia Fintech On MSMEs Performance: Mediation Of Interest In Use Of Transactions - Sri Wahjuni Latifah; Ahmad Waluya Jati (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This study was conducted to examine the use of Sharia fintech mediated by an interesting use of transactions to improve the performance of MSMEs. Methodology/approach: The survey was conducted on MSMEs in Malang Raya. The sampling technique using purposive sampling obtained 70 respondents. Data analysis and hypothesis testing using SEM assisted by Smart PLS software. Findings: The results showed that ease of use and trust have an effect on interest in using Sharia Fintech. However, service features and risk security have no effect on interest in transactions using Sharia fintech. This study proves that the use of Sharia Fintech with the mediation of interest in use is proven to have an effect on the performance of MSMEs. Practical implications: The implication of this research for MSMEs is that MSMEs should choose Sharia fintech under the supervision of the OJK. The implication for Sharia fintech companies is that they can create features that are easy for users to understand. Originality/value: This study offers a mediation model of interest in the use of transactions on the use of Sharia fintech and the performance of MSMEs